2016
DOI: 10.5812/aapm.34848
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Difficult Intubation Among Malay Patients in Indonesia

Abstract: BackgroundFailure to maintain an adequate airway can lead to brain damage and death. To reduce the risk of difficulty in maintaining an airway during general anesthesia, there are several known predictors of difficult intubation. People with a Malay background have different craniofacial structures in comparison with other individuals. Therefore, different predictors should be used for patients of Malay race.ObjectivesThe aim of this study was to determine the ability to predict difficult visualization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…). After detailed assessment, we included 133 studies (127 cohort type and six case–control) involving 844,206 participants . Of the 133 studies, there were six for the Mallampati test, 105 for the modified Mallampati test, six for Wilson risk score, 52 for thyromental distance, 18 for sternomental distance, 34 for the mouth opening test and 30 for the upper lip bite test.…”
Section: Resultsmentioning
confidence: 99%
“…). After detailed assessment, we included 133 studies (127 cohort type and six case–control) involving 844,206 participants . Of the 133 studies, there were six for the Mallampati test, 105 for the modified Mallampati test, six for Wilson risk score, 52 for thyromental distance, 18 for sternomental distance, 34 for the mouth opening test and 30 for the upper lip bite test.…”
Section: Resultsmentioning
confidence: 99%
“…HMDR reflects the occipito-atlantoaxial complex extension capacity [3]. HMDR has been used to estimate the size of the submandibular space [7]. From this point of view, this might seem to be static, but it is actually a dynamic parameter, as the submandibular space expands during laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Good sensitivity and specificity values were found by some authors 86.3-95.6% sensitivity and 69.2% specificity in non-obese patients [4,5]. Other studies confirmed moderate sensitivity of around 60% and lower specificity, suggesting that HMDR has little utility for difficult airway prediction [6,7]. A low sensitivity of 27.78% has also been reported for HMDR clin [8].…”
Section: Clinical Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…These complications are highly detrimental and endanger the patient's life. Therefore, it is extremely important to avoid a failed intubation [2].…”
Section: Introductionmentioning
confidence: 99%